한국 간호학 박사학위논문의 내용과 경향분석: 1982-2010년 양적 연구를 중심으로 - 이광자; 강윤희; 구미옥; 김경희; 김옥수; 서연옥; 서은영; 양수; 이은현; 이자형; 최명애; 하양숙; et al. (Journal of Korean Academy of Nursing, 2012)
Purpose: This study aimed to identify contents and trends of Korean nursing doctoral dissertations in terms of research methodology and theoretical characteristics. Methods: The design of the study was descriptive study and a total of 1,089 quantitative studies completed between 1982 and 2010 were reviewed using the analytical framework developed by the researchers. Results: The majority of studies utilized the experimental design (51.5%) and the others were survey design (38.8%) and methodological design (5.0%). Study subjects were shown as patients (45%), care givers (11.2%), ordinary persons (40.6%) and others (3.2%). There were growing trends in experimental design and patients as subjects. The prevailing data collection settings were hospitals (45.8%) and community (27.8%). The theoretical frameworks that studies were based on were the existing theories (37%) and a newly developed theoretical framework by a researcher (25.2%). a framework derived from other studies by the researcher (25.2%). Majority of studies (78.5%) employed a single theory as a theoretical framework. However, 31.8% of studies had no theoretical framework based on. Conclusion: Findings of this study provided the opportunities to shed new light on the current status of Korean doctoral dissertation and to deliberate on the future direction of nursing studies in Korea.